The potential antioxidant activity of ethanolic extract of Aceh ant-plant (Mymercodia sp) on the free radical DPPH(1,1-Diphenyl-2-pikrylhidrazil) - . Suryawati; . Frengki; Hijra Novia Suardi (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
This research aims to investigate the potential antioxidant activity of ethanolic extract of Aceh ant-plant (Mymercodia sp) on the free radical DPPH (1,1-diphenyl-2-pikrylhidrazyl). The ant-plant was extracted using maceration technique with the ethanol as solvent. The extract was made in various concentrations: 5, 10, 25, and 50 ppm. Then DPPH solution was added to it. Absorbance reading was conducted with spectrophotometry at the wave length of 517 nm after 30 minutes. The result of research shows the potency of ant-plant (Mymercodia sp) as an antioxidant free radical scavenging ethanolic extract with IC50 value of 14.73 ppm. The ascorbic acid as the control showed IC50 value of 7:32 ppm.